Yield and chemical properties of rubber of Hevea clones according to phenological stages - Silva, Juliano Quarteroli; Scaloppi Júnior, Erivaldo José; Moreno, Rogério Manoel Biagi; de Souza, Gilberto Batista; Gonçalves, Paulo de Souza; Scarpare Filho, João Alexio (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the yield performance and macronutrient content of rubber extracted from four Hevea brasiliensis clones, under different tapping systems and plant phenological stages. The experiment was carried out in the 2010 and 2011 crop seasons, in a split‑plot randomized complete block design, with four replicates. The main treatments – GT 1, PB 235, IAN 873, and RRIM 600 clones – were allocated in the plots, and the secondary treatments, which were the tapping systems ½S d/2, ½S d/4 ET 2.5%, and ½S d/7 ET 2.5%, were allocated in the subplots. The analyzed variables were natural rubber yield and macronutrient contents. Samples of natural rubber were obtained in the leaf development, mature leaf, and leaf senescence phenological stages. Rubber yield and its macronutrient contents are more influenced by tapping practice than by genetic material in the restrictive phenological stages of rubber foliage.